Radiation in the atmosphere : a course in theoretical meteorology - Zdunkowski, Wilford, 1929-; Trautmann, Thomas; Bott, Andreas, 1956- (Cambridge University Press, 2007)
Theory and applications of radiative transfer for graduate students and researchers in meteorology and related sciences.